2020
DOI: 10.1161/circep.119.008237
|View full text |Cite
|
Sign up to set email alerts
|

Granger Causality–Based Analysis for Classification of Fibrillation Mechanisms and Localization of Rotational Drivers

Abstract: Background: The mechanisms sustaining myocardial fibrillation remain disputed, partly due to a lack of mapping tools that can accurately identify the mechanism with low spatial resolution clinical recordings. Granger causality (GC) analysis, an econometric tool for quantifying causal relationships between complex time-series, was developed as a novel fibrillation mapping tool and adapted to low spatial resolution sequentially acquired data. Methods: Ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…As we have demonstrated for VF, it is possible that the degree of remodeling of the atrial substrate, including remodeling of ionic currents (Samie et al, 2001;Kneller et al, 2005;Muñoz et al, 2007), calcium handling (Samie et al, 2000), connexins, and fibrosis, determines the specific AF electrophenotype and the predominant AF mechanism. Our own analysis of human persistent AF would appear to support this hypothesis (Handa et al, 2020a).…”
Section: The Fibrillation Electrophenotype Spectrum -A Unifying Hypotmentioning
confidence: 66%
See 2 more Smart Citations
“…As we have demonstrated for VF, it is possible that the degree of remodeling of the atrial substrate, including remodeling of ionic currents (Samie et al, 2001;Kneller et al, 2005;Muñoz et al, 2007), calcium handling (Samie et al, 2000), connexins, and fibrosis, determines the specific AF electrophenotype and the predominant AF mechanism. Our own analysis of human persistent AF would appear to support this hypothesis (Handa et al, 2020a).…”
Section: The Fibrillation Electrophenotype Spectrum -A Unifying Hypotmentioning
confidence: 66%
“…There are currently several candidate approaches to identify the AF electrophenotype to guide tailored treatments. We recently adapted Granger causality analysis, originally an econometric tool for quantifying causal relationships between complex time series data (Nobel Prize Economics 2003), for use on AF data (Handa et al, 2020a). By testing for causal relationships of electrical signals between neighboring regions of the heart over time and quantifying the number of causal relationships above a set "causality threshold, " we can reliably measure global fibrillation organization and characterize the AF electrophenotype, even when applied to low spatial resolution clinical AF data (Figure 2).…”
Section: Mechanism-directed Treatment Based On Af Electrophenotypementioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that there is a range of AF and VF mechanisms, with varying degrees of the global organisation, using ex vivo optical mapping of explanted perfused hearts and invasive intracardiac mapping in patients undergoing AF ablation (Handa et al, 2020 ). Only some forms of AF are globally organised and driven by stable RDs, and these would be potentially amenable to ablation targeting RDs, while other forms of AF are globally disorganised with no clear drivers and as such may respond to compartmentalisation of the atria.…”
Section: Introductionmentioning
confidence: 99%
“…During persistent AF, the electrical activity is chaotic, and the identification of the wavefront propagation is not trivial. Granger causality has been proposed as a measurement that globally characterizes the organization of the wavefront propagation and maps rotational drivers using low spatial resolution sequentially acquired data [21]. However, it requires sequentially recorded segments longer than 2.5 seconds, which are not commonly found in clinical electrophysiology studies.…”
Section: Clinical Applicationsmentioning
confidence: 99%